Dermoglandular advancement-rotation flap for conservative treatment of breast cancer – description of technique, objective and subjective assessments - Soliani Bastos, Maria Carolina; Bagnoli, Fábio; Rinaldi, José Francisco; João, Thais Businaro Fernandes; de Oliveira, Vilmar Marques (Frontiers in Oncology, 2023)
Objective to describe and evaluate the dermoglandular advancement-rotation flap with no contralateral surgery as a technique for the conservative treatment of breast cancer when skin or a large proportion of gland requires resection. Patients/Methods 14 patients with breast tumors with a mean size of 4.2 cm and need for skin resection. The resection area is included within an isosceles triangle, with its apex located on the areola, which is the pivot for rotation of a dermoglandular flap released through a lateral extension along that triangle base. Symmetry before and after radiotherapy was objectively assessed by authors using the BCCT.core software, as well as subjectively by three experts and patients themselves using the Harvard scale. Results Experts considered the breast symmetry results to be excellent/good for 85.7% of patients in the early post-operative period and 78.6% in the late post-operative period. Excellent/good ratings provided by BCCT.core software amounted to 78.6% of cases in the early post-operative period and 92.9% in the late post-operative period. Symmetry was rated as excellent/good by 100% of patients. Conclusion Dermoglandular advancement-rotation flap technique with no contralateral surgery provides good symmetry when a large proportion of skin or gland requires resection on breast conservative cancer treatment.